Prevalence of burnout syndrome in workers of institution of the health sector - Tirso J. Hernández; Germán Sánchez; José F. Hernández; Edgar Vite (The International Journal of Management Science and Information Technology (IJMSIT), 2014)
The burnout syndrome was identified by Freudenberger in 1974, as a condition of fatigue or frustration that takes place for the dedication to a reason; it forms of life or relation that does not produce the awaited effort. The Burnout is characterized by emotional weariness, depersonalization and decrease or loss of the feeling of personal accomplishment. This problem derived from the stress that appears frequently in health professionals and there is propitiated by diverse organizational factors, which prevents the development of a labor harmonic environment and a suitable communication in the different hierarchic levels. The aim of this study consisted of determining the degree of prevalence of the burnout syndrome in the personnel of nursery and social work of a Public Health Hospital, as well as the determination of some predictive factors. The inventory was in use for measuring the burnout syndrome of Maslach which was applied to 227 nurses and 25 social workers. The principal results indicate a positive and significant correlation with the schedule of labors and with the number of patients who attend. Likewise, significant associations were identified by variables since it is the age and the marital status of the workers, which showed to have a negative correlation with regard to the dimensions of the syndrome of burnout. Finally there exists the need to realize interventions directed to reducing and eliminating the presence of the burnout syndrome in this type of personnel.
Keywords: 650; Syndrome of burnout; Emotional Depletion; Depersonalization; Low Personal Fulfillment